Polycyclic aromatic hydrocarbons (PAH) in gravity-operated and surface water from areas located nearby coking plant in Dąbrowa Górnicza (Upper Silesia region, Poland) = Wielopierścieniowe węglowodory aromatyczne (WWA) w wodach opadowych i powierzchniowych w rejonie zakładów koksowniczych w Dąbrowie Górniczej (woj. śląskie) - Kuna, Patrycja; Gwoździewicz, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of five PAHs contents determination in the surface and gravity-operated water. The samples of gravity-operated water were taken quarterly in 2009 from collectors put in fifteen points in areas located nearby coking plant in Dąbrowa Górnicza (Upper Silesia region, Poland). The results allowed determining the seasonal variability of PAHs concentration in gravity-operated water. Significant differences in concentration of PAHs in the summer and wintertime were observed. Moreover, to check the presence of PAHs contamination in the surface flowing water from selected streams, watercourses and draining system were collected.
Keywords: wielopierścieniowe węglowodory aromatyczne (WWA); wody opadowe; wody powierzchniowe; zanieczyszczenia WWA; PAH; gravity-operated water; surface water